Cost accounting practices in government organizations in Sarawak / Ibrahim Morshidi … [et.al.]. - Morshidi, Ibrahim; Mahat, Mohd Shah; Joseph, Corina (2007)
This exploratory study aims to evaluate the extent of cost accounting practices that have taken place in the government organizations in Sarawak. This study also aims to describe the budgetary control reporting and the role of cost accounting in cost reduction and control. Finally, this study seeks to identify the personal attributes of the respondents and the type of organizations that influences the application of advanced cost accounting techniques in government organizations in Sarawak. The questionnaires were distributed to personnel who handle cost and financial accounting functions in the government head quarters in Sarawak in 2004. Generally, it was found that costing for outputs or services, tender and contract-out jobs, budgetary control system and cost control and reduction measures are being practiced widely in the government organizations in Sarawak.